Ordinateur informatique automation : Journées d'étude 13 et 14 juin 1968 - Scheys, P.; Van Averbeke, C.; André, J. (Bruxelles: Union Nationale des Mutualités Socialistes (UNMS), 1968)
"par P. Scheys; C. Van Averbeke; J. Andre... et al."